Level of Knowledge of Bigball Games of Students State Junior High School 1, Simpang Empat, Martapura, Banjar Regency, South Kalimantan - Ahmad Rifa'i; Mita Erliana; H. M. Mulhim (Universitas Negeri Semarang, 2025)
The purpose of this study was to determine the level of knowledge of big ball games of students at State Junior High School 1 Simpang Empat Martapura, Banjar Regency, South Kalimantan. The method used in this study was descriptive quantitative. The population in this study was 300 and the sample was 124 (purposive sampling). The results of the study showed that the level of knowledge of big ball games of students at State Junior High School 1 Simpang Empat Martapura, Banjar Regency, South Kalimantan was in the very low category of 9 people (7%), the low category was 29 people (23%), the moderate category was 48 people (39%), the high category was 28 people (23%), and the very high category was 10 people (8%). The conclusion of the results of the study showed that the level of knowledge of big ball games of students at State Junior High School 1 Simpang Empat Martapura, Banjar Regency, South Kalimantan was in the moderate category.